Novel Mutations in ACP5 and SAMHD1 in a Patient With Pediatric Systemic Lupus Erythematosus - Hong, Soon-Min; Chen, Wei; Feng, Jiaqi; Dai, Dai; Shen, Nan (Frontiers in Pediatrics, 2022)
Background The study of genetic predisposition in pediatric systemic lupus erythematosus (pSLE) brought new insights into the pathophysiology of SLE as children are presumed to be greater genetic influenced. Moreover, identification of the genetic variants and linking the perturbed gene to the abnormal immune pathways and clinical manifestations can be beneficial to both diagnosis and therapy. Here in a patient with childhood-onset SLE, we identify the genetic alteration and analyzed the underlying immunological mechanism to support the diagnosis, prognosis and treatment in the future. Methods Whole exome sequencing (WES) was adopted for genetic analysis of a patient with childhood-onset SLE. Gene mutations were confirmed by Sanger sequencing. Clinical data of this patient were collected and summarized. Ingenuity Pathway Analysis was used to provide interacting genes of the perturbed genes. Online Enrichr tool and Cytoscape software were used to analysis the related pathways of these genes. Results We present the case of a 2-year-old girl who diagnosed of immune thrombotic thrombocytopenic purpura (iTTP) and SLE. This patient was characterized with skin bleeding spots in both lower limbs, thrombocytopenia, decreased serum complement levels, increased urine erythrocyte, positive ANA and dsDNA. This patient was treated with methylprednisolone and mycophenolate mofetil, but could not achieve clinical remission. Genomic analysis revealed 3 novel mutations in this pSLE patient with biallelic missense mutation (c.1152G>T and c.420G>A) at ACP5 and monoallelic (c.1423G>A) at SAMHD1. Bioinformatic analysis demonstrated these two genes and their interacting genes are enriched in regulation of multiple SLE-related immune pathways including cytokine signaling and immune cell activation or functions. Conclusion The combinatorial complexity of polymorphisms in ACP5 and SAMHD1 coding regions impacts SLE susceptibility. These genetic alterations may implicate the type I interferon pathway abnormality result may lead to the pathogenesis of SLE. Our research expanded the spectrum of ACP5 and SAMHD1 gene mutations. Identification of these mutations can help with genetic counseling diagnosis of SLE and proposed potential precision therapy targeting specific pathways.